Tratamento in vitro do colletotrichum brevisporum com plasma frio atmosférico associado à cera de carnaúba visando aplicação em pós-colheita de frutas - Costa, Isabely Keyva Fernandes (2018)
Several fruits have characteristics of high respiratory activity, which contributes significantly to a rapid maturation and to the development of pathogens in a short period of time, with consequent reduction in their post-harvest shelf life. Because of this, alternative control methods that increase the post-harvest shelf life of these fruits have been studied, such as the use of cold plasma at atmospheric pressure. In this sense, this work presented an experimental in vitro study with the objective to verify the action of cold plasma at atmospheric pressure by discharge of dielectric barrier (DBD), inactivation of Colletotrichum brevisporum present in several types of fruits, and to verify if the presence of carnauba wax coating would potentiate or reduce its action. Spores of this suspension fungus (100 ml solution containing 4 x 104 conidia × ml-1) were inoculated into both petri dishes containing BDA culture medium and potato dextrose agar (BDA) plates mixed with carnauba wax. The discharge was produced by pulses of electric voltage of 45 kV applied in the frequency of 405 Hz, during 9 minutes and characterized chemically by optical emission spectroscopy (OES). It was verified that the plasma was effective for both cases, with and without wax, immediately after inoculation of the fungi. Moreover, in the presence of the wax it was found that the plasma was effective even when applied immediately prior to inoculation of the suspension. These results indicate that DBD plasma with and without the use of carnauba wax showed efficiency in the inactivation of Colletotrichum brevisporum and that this technique is promising in antifungal control, with potential to replace traditional fungicides in the post-harvest phase, and the challenge is large-scale implementation and studies must be carried out with this goal